António Ferro, o retrato e a entrevista: montagem e propaganda na encenação da história - Serra, Filomena (Revelar: Revista de Estudos da Fotografia e Imagem, 2019)
The interviews of Antonio Ferro (1895-1956) to Salazar (1889-1970), gathered in the book Salazar, o Homem e a sua Obra [Salazar, the Man and his Work] (1933), inspired by the journalist Emil Ludwig's interviews to Stalin (1878-1953) and Mussolini (1883-1945), are still today the best written portrait of the Head of Government of the Portuguese Dictatorship. This portrait appears as a cinematographic montage made of fragments of images woven with words. It is not a portrait as an exclusive domain of memory, but an image of spectacle that transfigures. This book also becomes the portrait of the future head of the Secretary of National Propaganda, Antonio Ferro. Either a portrait or portraits, these "serialized interviews" served as a powerful propaganda instrument during the staging of the nation's History and, simultaneously, became a testamentary remark. Additionally, it emphasizes the use of photographic images with propagandistic intention, not only as an illustration, but also as a testimony of the different moments during the interviews, as well as the importance of the photographic iconography of the 193o's.